키토산-함유 제제 및 그의 제조 및 사용 방법 - MARTEINSSON RUNAR; LAUZON HELENE L; VIGFUSDOTTIR SIGRIDUR VIGDIS (2019)
본원에서 제공되는 것은 키토산-함유 제제, 이러한 제제의 제조 방법, 및 이러한 제제의 사용 방법이다. 본원에서 사용하기 위해 고려되는 키토산은 바람직하게는 고품질이며, 그의 공급원은 바람직하게는 갑각류 기원의 것이다. 본원에서 고려되는 제제는 수성이며, 액체- 또는 점성-유사성 중 어느 하나이고, 사용되는 키토산 및 산의 농도 및 유형이 가변성이며, 다른 성분들을 포함할 수도 있다. 그의 용도는 그를 필요로 하는 대상체 (예컨대 인간 또는 동물) 또는 심지어는 식료품에 대한 경구/치과적 투여 또는 국소/표면 적용을 위한 것으로 다양하며, 그것이 적용되는 곳의 우수한 상태를 유지하는 것, 또는 건강 증진, 치유, 질환 예방 또는 치료에 기여하는 것을 목표로 한다. 본 발명은 또한 다른 생성물의 제제에 사용될 수 있는 농축된 용액에 관한 것이다. Provided herein are chitosan-containing formulations, methods of making such formulations, and methods of using such formulations. Chitosan contemplated for use herein is preferably of high quality and its source is preferably of crustacean origin. The formulations contemplated herein are aqueous, either liquid- or viscous-like, varying in concentration and type of chitosan and acid used, and may include other components. Their uses are diverse, for oral/dental administration or topical/surface application to subjects (e.g. humans or animals) in need thereof or even food commodities, aiming to maintain a good condition where it is applied or contributing to health enhancement, healing, disease prevention or treatment. The present invention also relates to concentrated solutions that may be used for the formulation of other products.